Predictors and consequences of presenteeism: a study of nurses in Maltese geriatric settings - Fiorini, Luke Anthony (2019)
Background: Most commonly conceptualised as attending work whilst ill, sickness presenteeism (SP) contrasts with sickness absence (SA), which involves avoiding work when ill. Due to shortcomings in SP research and theory, its predictors and consequences remain unclear. The healthcare sector experiences a particularly high prevalence of SP. Despite this, SP and its consequences have not been studied in a healthcare setting in Malta.